Langkah Awal Menuju Stabilitas Ekonomi pada Siswa SMA Swasta Nurcahaya Kota Medan - Fachrun Nissa; Nirma Rosalia; Retno Nela Simanjuntak; Muhammad Harpis (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Individual economic stability is a crucial prerequisite for achieving well-being and financial independence. The Community Service Program (PKM) titled "Initial Steps Towards Economic Stability for Students of SMA Swasta Nurcahaya Kota Medan" aims to enhance students' financial literacy and entrepreneurial skills through socialization and discussion. This activity involved introducing the basic concepts of economic stability, personal financial management, and simple entrepreneurial initiatives. The results showed positive responses, with increased student understanding of financial literacy, awareness of the importance of personal economic stability, and interest in starting small businesses. These findings indicate that the program successfully motivated students to create simple financial plans and be more attentive to economic conditions. This step serves as a significant foundation for preparing students to face future economic challenges.